Management of the multi-ligamentous injured knee: an evidence-based review - Samuel, Linsen T.; Rabin, Jacob; Jinnah, Alex; Rosas, Samuel; Chao, Linda; Sullivan, Rashad; Gwam, Chukwuweike U. (Annals of Joint; Vol 4 (March 2019): Annals of Joint, 2019)
Multi-ligamentous knee injury (MLKI) can be a devastating injury, resulting in long-term knee instability and loss of function. For patients with MLKI, areas of controversy persist on how to best optimize outcomes. These areas of contention are often centered operative timing and technique with the aims of restoring patient function, knee range of motion, and stability. Currently, a paucity of studies exists that can be used to direct orthopedists on how to manage MLKI patients. This review critically analyzes literature in attempts to equip readers with best options for managing patients with MLKI.